Determinant Factors of Quality and Quantity Consumed of Livestock Products Consumption in Indonesia - Muzayyanah, Mujtahidah Anggriani Ummul; Sulastri, Endang; Joshi, Niraj Prakash (Buletin Peternakan, 2026)
Consumption of livestock products has increased compared to fish-based protein foods. Food quality, especially animal protein foods, is critical in determining nutritional adequacy to reduce the high incidence of chronic and acute malnutrition. This study emphasizes how much the income of households needs to increase in order for them to achieve optimal nutritional well-being. Consumption of livestock products as a source of animal protein food in Indonesia is sensitive to changes in price and income. As people's wealth increases, they have the chance to consume a greater quantity and higher quality of these foods. This study examines the influence of increasing income on the quality of animal protein from livestock products consumed in association with socioeconomic and demographic determinants of households and the income elasticity of demand for the quantity and quality of these foods. National household survey data were used in this study. Based on Engel’s framework, the basic analysis is used to analyze the quantity and quality of animal protein food demand. The findings showed that income and household sociodemographics affected the expenditure and quantity demanded of beef, chicken, and eggs. Estimation of expenditure, quantity, and quality elasticity showed the consumer concerned about quantity compared to quality, but different for high-income households, which tend to be concerned with better quality products. Development strategies focus on increasing opportunities to generate income and improve the quality of livestock products.